1987
DOI: 10.1126/science.2888190
|View full text |Cite
|
Sign up to set email alerts
|

The tat Gene of Human T-Lymphotropic Virus Type 1 Induces Mesenchymal Tumors in Transgenic Mice

Abstract: Human T-lymphotropic virus type 1 (HTLV-1) is a suspected causative agent of adult T-cell leukemia. One of the viral genes encodes a protein (tat) that not only results in transactivation of viral gene expression but may also regulate the expression of certain cellular genes that are important for cell growth. Transgenic mice that expressed the authentic tat protein under the control of the HTLV-1 long terminal repeat were generated, and cell types that are permissive for the viral promoter and the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
294
0
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(308 citation statements)
references
References 42 publications
6
294
0
3
Order By: Relevance
“…Another interesting facet of Tax is its ability to transform cells. The oncogenic properties of this protein have been established by various assays, including transformation of primary T lymphocytes (Grassmann et al, 1989), cooperation with Ras in transformation of ®broblasts (Pozzatti et al, 1990) and induction of tumours in transgenic mice (Nerenberg et al, 1987;Benvenisty et al, 1992;Grossman et al, 1995). Tax transgenic mice are also known to develop several pathologies including thymus atrophy (Furuta et al, 1989), muscle degeneracy (Nerenberg and Wiley, 1989), arthritis (Iwakura et al, 1991) and a proliferation of ductal cells of the salivary gland resembling the SjoÈ gren syndrome (Green et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting facet of Tax is its ability to transform cells. The oncogenic properties of this protein have been established by various assays, including transformation of primary T lymphocytes (Grassmann et al, 1989), cooperation with Ras in transformation of ®broblasts (Pozzatti et al, 1990) and induction of tumours in transgenic mice (Nerenberg et al, 1987;Benvenisty et al, 1992;Grossman et al, 1995). Tax transgenic mice are also known to develop several pathologies including thymus atrophy (Furuta et al, 1989), muscle degeneracy (Nerenberg and Wiley, 1989), arthritis (Iwakura et al, 1991) and a proliferation of ductal cells of the salivary gland resembling the SjoÈ gren syndrome (Green et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Tax expression is sufficient to immortalize primary human CD4-positive T cells and transform rat fibroblast cell lines in vitro, 4,5 and is capable of inducing tumors in transgenic mice. 6 However, the exact mechanisms through which Tax exerts its oncogenic effects are not fully understood. Tax was originally identified as a transcriptional activator of the HTLV-I promoter in LTR, 7 but subsequent studies identified numerous other activities, including modulation of the expression of several cellular genes involved in cellular proliferation, such as genes for growth factors, growth factor receptors, cytoplasmic signal transmitters and nuclear transcription factors.…”
mentioning
confidence: 99%
“…24 Tax also transforms rodent fibroblast cell lines and induces tumors in its transgenic mice. 25,26 Through all of these activities, Tax acts as a powerful oncogene and represents a very attractive viral protein for targeted therapy. However, among the wideranging properties of Tax oncoprotein, activation of the NF-kB pathway plays a crucial role in the proliferation and transformation of the infected cells, and hence also represents a critical therapeutic target.…”
Section: Microenvironmentmentioning
confidence: 99%